2016
DOI: 10.1007/s10544-016-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile modulation of cell adhesion to a poly(ethylene glycol) diacrylate film with incorporation of polystyrene nano-spheres

Abstract: Poly(ethylene glycol) diacrylate (PEGDA) is a common hydrogel that has been actively investigated for various tissue engineering applications owing to its biocompatibility and excellent mechanical properties. However, the native PEGDA films are known for their bio-inertness which can hinder cell adhesion, thereby limiting their applications in tissue engineering and biomedicine. Recently, nano composite technology has become a particularly hot topic, and has led to the development of new methods for delivering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Surface roughness is an important factor affecting cell adhesion behavior [23][24][25]. Some early studies have found that surface roughness may affect cell adhesion behavior regardless of the cell type and matrix materials ( Figure 1).…”
Section: Roughness Of Substrate Surfacesmentioning
confidence: 99%
“…Surface roughness is an important factor affecting cell adhesion behavior [23][24][25]. Some early studies have found that surface roughness may affect cell adhesion behavior regardless of the cell type and matrix materials ( Figure 1).…”
Section: Roughness Of Substrate Surfacesmentioning
confidence: 99%
“…[ 11,93–95 ] Indeed, surface modifications that increase the nanoscale roughness of electrospun fibers have been reported to improve cell attachment, differentiation and proliferation regardless of cell type. [ 84,89,96 ] A recent study also showed how melanin‐based electroactive and antioxidant silk‐fibroin nanofibrous scaffolds displayed neuroprotective properties, and improved cell proliferation and differentiation of neuroblastoma cells. [ 23 ] Taken together, our data suggests the suitability and potential advantages of melanin‐PHB scaffold as a brain‐tissue‐like biomaterial, which could be deployed to repair damaged neural tissue and support the regrowth of severed nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the surface roughness of these membranes fell in a macroscopic range. Previous studies demonstrated the effect of surface roughness on cellular adhesion regardless of the cell types [6,28,29]. Increased adhesion of fibroblast cells was observed on the surface of polymeric biomaterial with macroscopic irregularities, as these cells were able to spread and grow on the surface [4].…”
Section: Surface Morphology Of Microwave-dried Gelatin Membranesmentioning
confidence: 97%